The pregnant widow - Amis, Martin (Alfred A. Knopf, 2010)
The year is 1970, and it's a long, hot summer. In a castle on a mountainside in Italy, half a dozen young lives are afloat on a sea of change, trapped inside the history of the sexual revolution. The girls are acting like boys, the boys are going on acting like boys, and Keith Nearing - twenty years old, a literature student all clogged up with the English novel - is struggling to twist feminism and women's ascendency toward his own ends. As revolutions go, this one might have been nonviolent, but it wasn't bloodless - and now, in the twenty-first century, the events of 1970 and their repercussions are finally catching up with Keith Nearing.